Pengembangan Kecerdasan Naturalistik pada Anak Usia Dini - Wulandari, Nani Tri; Lamanaura, Yepota Nossa; Agustina, Erina Dwi (STKIP PGRI Ponorogo Press, 2024)
Intelligence is a person’s ability to solve problems, be able to adapt to new situations, and also be able to learn lessons from experience. Every individual has various intelligences, one of which is naturalist intelligence. This article reviews the development of naturalistic intelligence in early childhood. This type of research uses a type of library or library research. Meanwhile, the data collection technique used is literature data collection. The development of naturalistic intelligence can be done using various methods, depending on the child’s abilities and facilities. The development of naturalistic intelligence in early childhood can be developed by: (1) inviting children to do outdoor activities (2) gardening and caring for plants (3) observing animals and their habitats (4) visiting museums related to nature (5) utilizing natural media in learning (6) creating educational games in nature (7) implementing project-based learning.